2010
DOI: 10.1086/657311
|View full text |Cite
|
Sign up to set email alerts
|

Protective Efficacy of Seasonal Influenza Vaccination against Seasonal and Pandemic Influenza Virus Infection during 2009 in Hong Kong

Abstract: ClinicalTrials.gov number NCT00792051 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
167
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(180 citation statements)
references
References 58 publications
13
167
0
Order By: Relevance
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 4,372 studies initially identified (Figure), 18 RCTs [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39], 14 non-randomised clinical trials [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and six observational studies [54][55][56][57][58][59] were eligible for inclusion. The clinical trial registry search yielded 12 additional relevant studies (five RCTs and seven nonrandomised trials).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple study designs were encountered in terms of comparison groups; for non-adjuvanted TIV, comparison with placebo was only found in one study [33]. Five studies examined adjuvanted vaccines (MF59 or virosomal adjuvant) in at least one study arm [30,31,34,35,39].…”
Section: Characteristics Of Randomised Controlled Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seasonal influenza vaccination provided 20–77% in children depending on antigenic match, against laboratory‐confirmed influenza (Table 2). 18, 47, 48, 49, 50, 51, 52, 53, 54, 55 Vaccinating school children provided 23·3% (66·3–74·9) protection against influenza and indirect protection of 61% (5·8–84·7) for household contacts 56. Vaccinating pregnant women prevented laboratory‐confirmed influenza in both mothers (50%) and their infants up to 6 months of age (49–63%) 57, 58.…”
Section: Resultsmentioning
confidence: 99%